2014
DOI: 10.1002/mus.24272
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative muscle ultrasound and quadriceps strength in patients with post‐polio syndrome

Abstract: Quantitative ultrasound distinguishes healthy muscles from those affected by PPS, and measures of muscle quality and quantity are associated with muscle strength. Hence, ultrasound could be a useful tool for assessing disease severity and monitoring changes resulting from disease progression or clinical intervention in patients with PPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
3
15
0
1
Order By: Relevance
“…Echo intensity has gained popularity as a measurement of muscle quality (Melvin et al 2014;Watanabe et al 2013) and/or muscle damage (Chen et al 2012;Gonzalez-Izal et al 2014;Radaelli et al 2012), and has been used to assess changes related to aging (Fukumoto et al 2012b), neuromuscular disorders (Arts et al 2011;Bickerstaffe et al 2015;Pillen et al 2008Pillen et al , 2009) and exercise interventions Radaelli et al 2013). However, like that of mCSA, the measurement of EI with panoramic US imaging may be AC 5 arm circumference; aSKF 5 anterior skinfold thickness; CV (%) 5 coefficient of variation; EI P 5 panoramic image echo intensity; EI ST 5 single transverse image echo intensity; FT 5 fat thickness; ICC 2,1 5 intra-class correlation coefficient, model 2,1; ICC 2,1 95% 5 95% confidence interval for ICC 2,1 ; mCSA 5 mean cross-sectional area; MD 5 minimum difference needed to be considered real; MD (%) 5 minimum difference needed to be considered real expressed as a percentage of the grand mean; MS B (%) 5 mean square between patients expressed as a percentage of the grand mean; MT 5 muscle thickness; p-value 5 type 1 error rate for the one-way repeated-measures analysis of variance used to assess systematic variability; SEM 5 standard error of measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Echo intensity has gained popularity as a measurement of muscle quality (Melvin et al 2014;Watanabe et al 2013) and/or muscle damage (Chen et al 2012;Gonzalez-Izal et al 2014;Radaelli et al 2012), and has been used to assess changes related to aging (Fukumoto et al 2012b), neuromuscular disorders (Arts et al 2011;Bickerstaffe et al 2015;Pillen et al 2008Pillen et al , 2009) and exercise interventions Radaelli et al 2013). However, like that of mCSA, the measurement of EI with panoramic US imaging may be AC 5 arm circumference; aSKF 5 anterior skinfold thickness; CV (%) 5 coefficient of variation; EI P 5 panoramic image echo intensity; EI ST 5 single transverse image echo intensity; FT 5 fat thickness; ICC 2,1 5 intra-class correlation coefficient, model 2,1; ICC 2,1 95% 5 95% confidence interval for ICC 2,1 ; mCSA 5 mean cross-sectional area; MD 5 minimum difference needed to be considered real; MD (%) 5 minimum difference needed to be considered real expressed as a percentage of the grand mean; MS B (%) 5 mean square between patients expressed as a percentage of the grand mean; MT 5 muscle thickness; p-value 5 type 1 error rate for the one-way repeated-measures analysis of variance used to assess systematic variability; SEM 5 standard error of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…EI has attracted attention as a method to non-invasively investigate the tissue composition of muscle as a surrogate measure of muscle quality (Arts et al 2012;Bickerstaffe et al 2015;Pillen et al 2009;Radaelli et al 2013;Reimers et al 1993b;Rosenberg et al 2014). For example, Reimers et al (1993b) reported that EI was positively related to intramuscular fat content in men with various neuromuscular diseases.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite this, ultrasound imaging allows for a quick and accurate assessment of individual muscle architectural characteristics and has been shown to correlate well with MRI in healthy populations . In addition to this, there are now a growing number of studies showing that the architecture of the lower extremities [most commonly the rectus femoris (RF)] assessed by ultrasound is associated with physical performance in older and other clinical populations …”
Section: Introductionmentioning
confidence: 99%
“…13,15,16 In addition to this, there are now a growing number of studies showing that the architecture of the lower extremities [most commonly the rectus femoris (RF)] assessed by ultrasound is associated with physical performance in older and other clinical populations . [17][18][19] In CKD populations, ultrasound has recently been used to identify the presence of low muscle mass, measured as quadriceps thickness, in end stage renal disease patients receiving haemodialysis. 20 We have shown that ultrasound-derived RF-CSA is associated with physical performance amongst patients with CKD stages 3b-5 not requiring dialysis.…”
Section: Introductionmentioning
confidence: 99%